Evaluation of the Prevalence of Chronic Kidney Disease and Rates of Oral Antidiabetic Prescribing in Accordance with Guidelines and Manufacturer Recommendations in Type 2 Diabetic Patients within a Long-Term Care Setting - Ning Wu; Xia Yu; Mallik Greene; Gary Oderda (International Journal of Nephrology)
This retrospective study assessed the prevalence of moderate to severe chronic kidney disease (CKD) among nursing home (NH) residents with type 2 diabetes. The pattern of oral antidiabetic drug (OAD) use and their concordance with the National Kidney Foundation (NKF) guideline and prescribing information (PI) was also assessed. About half (47%) of diabetic residents had moderate to severe CKD. A little over a quarter of the 186 residents using OADs received at least one NKF-discordant OAD prescription. Metformin was the most commonly misused OAD. PI nonconcordance was observed in 58.6% of residents and was highest in glipizide and metformin users. With the high prevalence of moderate to severe CKD in NH residents with diabetes, physicians should consider residents’ renal function when choosing treatment plans and review treatments regularly to check compliance with the NKF guidelines or PIs.